The impact of sex on left ventricular cardiac adaptations to endurance training: a systematic review and meta-analysis - Diaz-Canestro, C.; Montero, D. (Sports Medicine, 2020)
Background and Objective: The left ventricle (LV) entrains major prognostic factors amenable to substantial modification with endurance training (ET). Whether LV adaptations to ET are sex-dependent remains uncertain. The aim of this study was to perform a systematic review and meta-analysis to determine the influence of sex on LV adaptations to ET. Methods: We conducted a systematic search of MEDLINE and Web of Science since their inceptions until September 2019 for articles assessing the effect of ET (<= 12 weeks) on LV structure and/or function in healthy men and women. Meta-analyses were performed to determine the mean difference in LV variables between post and pre training measurements. The impact of sex and potential moderating factors was assessed by subgroup and meta-regression analyses. Results: Twenty-six ET studies were included after systematic review, comprising a total of 468 healthy untrained individuals (m = 287, f = 181; age = 22-72 years). ET programs mainly included lower body endurance exercise of moderate intensity ranging from 12 to 52 weeks of duration. ET characteristics did not differ between studies in men and women. After data pooling, LV end-diastolic volume (LVEDV) was increased to a greater extent in men compared with women (+15.6 vs. +5.2 ml. P<0.004), while LV stroke volume (SV) was only enhanced in men (+9.2 ml, P = 0.006). In contrast, LV mass (LVM) was similarly augmented in men and women (+10.2 vs. +7.0 g. P = 0.50). In meta-regression analyses, negative linear relationships were detected between age and LV adaptations (LVEDV, SV, LVM) in women (P <= 0.034) but not in men. Conclusion: Pooled evidence demonstrates markedly blunted and distinct moderating factors of key LV functional adaptations in women compared with men, despite both sexes presenting a similar LV hypertrophic response to ET.